Whether the Effect of Sperm DNA Fragmentation on the Clinical and Laboratory Outcomes Changes with the Paternal age in the intracytoplasmic sperm injection Cycles of Donor Oocytes - Deepthi Repalle; saritha kv; Shilpa Bhandari; Jitendra Choudhary (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The present study aimed to know the effect of paternal age together with Sperm DNA fragmentation on the clinical and laboratory outcomes in the donor oocyte intracytoplasmic sperm injection cycles.